Identifikasi Karakteristik Morfologi dan Kandungan dari Famili Rutaceae di Daerah Jabong, Kota Subang, Jawa Barat. (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2024)
One of the families of the Rutaceae family is the orange. But only three categories are mandarin, big orange, and lemon orange that are considered genuine orange. Citrus aurantifolia, lemon (Citrus limon L.), and lemon orange (Citrus jambhiri) are cross-fruit fruits of the original orange. The purpose of this research is to find out the variety of species and morphology of citrus plants (Citrus sp) that are in the Jabong region, Subang, West Java. The methods used in this research include field surveys, qualitative methods and descriptive methods of morphological analysis to determine existing species and varieties. Research results show that the Subang region has a significant diversity of the Citrus sp. family, with the discovery of several species such as Citrus aurantiifolia, Citrus limon, and Citrus jambhiri. (jeruk limau). Morphological analysis reveals variations in the size, shape, and color of the fruit. Such diversity demonstrates the great potential to produce superior orange cultivars of high commercial value and environmental adaptability to local conditions.